1986
DOI: 10.1017/s0021859600063309
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the gravid uterus, foetus and utero-placenta at several stages of gestation in cows

Abstract: To quantify changes in rates of metabolism and nutrient uptake of gravid uteiine, foetal and utero-placental tissues throughout gestation, mature Hereford cows received surgery at 132 ±0-6 (w = 12), 176 + 0-5 (n = 8), 220 ±0-4 (n = 11) and 245 ±1-5 (n = 7) days after mating. Indwelling catheters were implanted into a uterine artery and vein of all cows. Foetal catheters also were implanted into an umbilical vein and foetal femoral artery and vein (days 176 and 220) or into a placental artery and two placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 23 publications
7
49
1
1
Order By: Relevance
“…In the cow, caruncular vascular development continues throughout gestation (Hutchinson, 1962). Rates of uterine and umbilical blood flows also increase throughout gestation (Reynolds et al, 1986). In addition, rate of placental blood flow is an important determinant of the rate of transplacental exchange (Bell et al, 1986; The present paper and also a previous report (Reynolds et al, 1987b) indicate that stimulatory angiogenic activity is produced primarily by maternal placental tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cow, caruncular vascular development continues throughout gestation (Hutchinson, 1962). Rates of uterine and umbilical blood flows also increase throughout gestation (Reynolds et al, 1986). In addition, rate of placental blood flow is an important determinant of the rate of transplacental exchange (Bell et al, 1986; The present paper and also a previous report (Reynolds et al, 1987b) indicate that stimulatory angiogenic activity is produced primarily by maternal placental tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that size ofthe placental blood supply is a primary determinant of the rate of physiological exchange between the maternal and fetal systems (Bell et al, 1986;Reynolds et al, 1986;. Conditions associated with reduced rate of fetal growth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, a 2.5-fold increase was reported between day 24 and 30 of gestation [28]. In sheep, UBF increases linearly over time during the For instance, Reynolds et al [49] showed that UBF increased until 250 days of gestation in cows by using the steady-state diffusion procedure with deuterium oxide, whereas Ferrell and Ford [20] did not find any increase of UBF after day 178 when measured with electromagnetic transducers. Moreover, UBF varies with time during the same day, with sow position, and between night and day (Père, unpublished data), and it was measured during 10 min per day by Ford et al [26] and Reynolds et al [48] instead of 24 h as in the present study.…”
Section: Variation Of Ubf With Pregnancy Stagementioning
confidence: 98%
“…kg -1 FPU does not change during the second half of pregnancy, which means that absolute UBF increases. In cows, Reynolds et al [49] and Reynolds and Ferrell [45] reported that UBF increases exponentially during gestation (4.5-fold greater at 250 than at 137 days of gestation). All these results show that uterine blood flow increases during a period of intense development and growth of the foetuses.…”
Section: Effect Of Number Of Foetuses In the Uterine Hornmentioning
confidence: 99%
“…Placental weight and birth weight are highly correlated in cattle (Anthony et al, 1986b;Echternkamp, 1993;Zhang et al, 1999); however, the functional capacity of the placenta is closely related to placental perfusion. Bovine uterine and umbilical blood flow increases exponentially during the second half of gestation, which equates to relatively constant rates of umbilical blood flow on a foetal weightspecific basis during this period (Reynolds et al, 1986). A more detailed account of placental function and metabolism in cattle is provided by Ferrell (1989), and of foetal macronutrient requirements and metabolism in cattle and sheep, and of placental function and metabolism, by Bell et al (2005).…”
Section: Normal Bovine Conceptus Growth and Metabolismmentioning
confidence: 99%